Highly flexible and transferable supercapacitors with ordered three-dimensional MnO2/Au/MnO2 nanospike arrays1. Issue 19 (21st May 2015) - Gao, Yuan; Jin, Huanyu; Lin, Qingfeng; Li, Xiang; Tavakoli, Mohammad Mahdi; Leung, Siu-Fung; Tang, Wing Man; Zhou, Limin; Wa Chan, Helen Lai; Fan, Zhiyong
<x xml:space="preserve">Abstract</x> An ultra-thin freestanding Au NSP film is fabricated by simple wet etching. Supercapacitors fabricated based on such structure show notable electrochemical improvements.